THEMATIC GROUPS OF ANTHROPONYMS USED IN “BOBURNOMA” (Eureka Journal of Education & Learning Technologies, 2026)
The article analyzes the lexical-semantic features and classification of anthroponyms found in Baburnama and examines their role in the development of Uzbek anthroponymy.
Keywords: Anthroponymy, onomastics, Uzbek anthroponyms, Baburnama, historical anthroponyms, classification of personal names, religious anthroponyms, personal names, lexical-semantic features of anthroponyms, Uzbek onomastic studies.